1991
DOI: 10.1007/bf03222724
|View full text |Cite
|
Sign up to set email alerts
|

Codepositing elements by halide-activated pack cementation

Abstract: The codeposition of two or more elementli in II halide-activated cementation pack is inherently difficult because of large differences in the thermodynamic stabilities for tlreir volatile halides. However, through II computer-assisted analysis of the pack equilibria, combiniltions of suitable masteralloys and activator salts can be identified. The codepositwn of chromium plusaluminum or chromium plus silicon by pack cementation has yielded diffusion coatings with excellent resistance to higll-tempemtureoxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 2 publications
0
29
0
3
Order By: Relevance
“…Application of coating in the form of a slurry followed by vacuum diffusion treatment has also been reported [14]. Among all the methods, halide activated pack cementation (or simply, pack cementation) has been the most widely used process for application of silicide coating on refractory metals, including niobium [5,6,[15][16][17][18]. In this method, which is actually a variant of chemical vapour deposition (CVD) technique, the substrate is kept immersed in a powder pack and heated to a high temperature in an inert atmosphere for the formation of the coating [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of coating in the form of a slurry followed by vacuum diffusion treatment has also been reported [14]. Among all the methods, halide activated pack cementation (or simply, pack cementation) has been the most widely used process for application of silicide coating on refractory metals, including niobium [5,6,[15][16][17][18]. In this method, which is actually a variant of chemical vapour deposition (CVD) technique, the substrate is kept immersed in a powder pack and heated to a high temperature in an inert atmosphere for the formation of the coating [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the protection of Nb-alloys at high temperatures is achieved by application of oxidation resistant coatings. It has been reported that Nb-based bulk intermetallics such as aluminides and silicides possess improved oxidation resistance because of their ability to form protective scale such as Al 2 O 3 or SiO 2 [3][4][5][6]. These compounds can be applied in form of coatings to enhance the oxidation resistance of Nb-alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Cl2, then continues to react with metal powders left in the powder packs till the activity of metals in powder pack become equilibrium with that at steel surface. Therefore, halide activator plays an important role to control the vapor pressures of metal halides in powder packs 21) which maintain the activity of diffusing metals at specimen surface to sustain the diffusion with aids of gaseous reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Since the partial pressures of Alhalides are normally much higher than those of Cr-halides, the coatings of Cr-Al alloys are only possible when the activity of Al in the pack is 2-3 orders below that of Cr. [18][19][20] There are two possible ways to overcome this problem: (1) using a "lean" pack where the metal powders contain higher Cr and lower Al concentrations; 21,22) or (2) performing dual instead of single heating processes first by treating at 925°C and then at 1 150°C. 20) Meanwhile, chromium carbide (Cr23C6) was reported to form at surface due to the rapid outward diffusion of carbon during simultaneously chromizing and aluminizing.…”
Section: Introductionmentioning
confidence: 99%
“…However, Nb-base alloys are susceptible to rapid oxidation scaling and embrittlement by oxygen dissolution at high temperatures [1]. While there have been attempts to enhance oxidation resistance with component alloying, a satisfactory balance of mechanical properties and oxidation resistance at high temperatures have not been reached so far [2,3]. The silicide coatings greatly increase the heat resistance of niobium alloys at temperatures up to 1600°C [4].…”
Section: Introductionmentioning
confidence: 99%